1989
DOI: 10.1002/ana.410260303
|View full text |Cite
|
Sign up to set email alerts
|

Mossy fiber synaptic reorganization in the epileptic human temporal lobe

Abstract: The distribution of the mossy fiber synaptic terminals was examined using the Timm histochemical method in surgically excised hippocampus and dentate gyrus from patients who underwent lobectomy of the anterior part of the temporal lobe for refractory partial complex epilepsy. The dentate gyrus of epileptic patients demonstrated intense Timm granules and abundant mossy fiber synaptic terminals in the supragranular region and the inner molecular layer. In contrast, the dentate gyrus of presenescent nonepileptic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
574
2
13

Year Published

1992
1992
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,080 publications
(617 citation statements)
references
References 16 publications
27
574
2
13
Order By: Relevance
“…Increasing the total number of connections results in higher frequency behaviour, and greater numbers of cells undergoing action potentials at any given time point. One interpretation for this increase in connectivity could be the axonal branch sprouting behaviour that is observed in human and animal models in both neocortex and mesial temporal structures (Sutula 2002;Longo et al 2003;Vijayalakshmi et al 2005;Sutula et al 1989;Carmichael et al 2001). Future studies of epileptic foci might incorporate isolated regions of higher connectivity representing a seizure focus adjoining regions of less excitable modeled tissue to study the spread of epilepsy into normal brain.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the total number of connections results in higher frequency behaviour, and greater numbers of cells undergoing action potentials at any given time point. One interpretation for this increase in connectivity could be the axonal branch sprouting behaviour that is observed in human and animal models in both neocortex and mesial temporal structures (Sutula 2002;Longo et al 2003;Vijayalakshmi et al 2005;Sutula et al 1989;Carmichael et al 2001). Future studies of epileptic foci might incorporate isolated regions of higher connectivity representing a seizure focus adjoining regions of less excitable modeled tissue to study the spread of epilepsy into normal brain.…”
Section: Discussionmentioning
confidence: 99%
“…Microtubules are very abundant in the brain and tubulin is an in vitro and in vivo substrate of PIMT (Ohta et al 1987;Najbauer et al 1996). Previous studies on human epilepsy have reported mossy fiber synapse reorganization and dendrite swelling due to alteration in the normal arrangement of microtubules in temporal lobe epilepsy (Vaquero et al 1982;Sutula et al 1989). In addition, the pyramidal neurons of PIMT-/-mice show abnormal dendrite arborization and microtubule disorganization (Yamamoto et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Selective effects of NR2A and NR2B antagonists on mossy fiber sprouting Activation of NMDARs has been implicated in seizure-induced mossy fiber sprouting, which is also a feature of human limbic epilepsy (Sutula et al, 1989;Houser et al, 1990;Sutula et al, 1996). It is thus of interest to determine whether the selective impediment of epileptogenesis by NR2A antagonist is also reflected in seizure-induced mossy fiber sprouting, which normally occurs a few weeks after SE.…”
Section: Effects Of Nr2a and Nr2b Antagonists On Se-induced Neuronal mentioning
confidence: 99%
“…Timm staining is used to visualize mossy fiber reorganization in the inner molecular layer of dentate gyrus that accompanies epileptogenesis (Sutula et al, 1989;Cavazos et al, 1991). Rats surviving up to 8 weeks after SE or 10 times constitutive class 5 seizures in kindling were deeply anesthetized by an overdose chloral hydrate and perfused for 2 min with 0.9% NaCl, 5 min with sulfide solution, and 30 min with 4% paraformaldehyde in 0.1 M phosphate buffer, pH 7.4.…”
Section: Introductionmentioning
confidence: 99%